Acute encephalopathy in children in Muzaffarpur, India: a review of aetiopathogenesis. (8th June 2020) - Sarkar, Abhirup; Datta, Debatri; Datta, Sudip Kumar; John, T Jacob
Abstract: The acute encephalopathy occurring in children in Muzaffarpur, India, also recognised in other litchi-cultivating areas of India, Bangladesh, Vietnam and China, had previously been linked to litchi consumption. Recently, it has been identified as hypoglycaemic encephalopathy of an unusual aetiology with three key factors: undernutrition, prolonged fasting and litchi consumption. A second set of investigators has independently reconfirmed the diagnosis and the three-factor aetiology. Skipping the evening meal with an intake of large amounts of litchi in undernourished children is causative. Early-morning hypoglycaemia with an inadequate glycogen store leads to initiation of gluconeogenesis and fatty acid β-oxidation, but methylene cyclopropyl alanine and glycine present in the litchi aril block the fatty acid β-oxidation cycle. The outcomes are uncorrected hypoglycaemia and encephalopathy due to the entry of metabolic intermediates that cross the blood-brain barrier and affect neuronal function. Suggested measures include early 10% dextrose infusion. Awareness about the disease is of prime importance. The diagnosis and aetiopathogenesis are still under question from a part of the scientific community. This review was undertaken to present a comprehensive view of hypoglycaemic encephalopathy and to remove some of the lingering doubts.